A case of tracheal chondrosarcoma - M. D. Ter-Ovanesov; A. A. Aksarin; S. M. Kopeyka (Сибирский онкологический журнал, 2025)
Background. Chondrosarcoma of the trachea is an extremely rare malignant tumor, accounting for only 0.1 % of all tracheal tumors. It is believed that chondrosarcoma arises from malignant degeneration in mesenchymal pluripotent cells of cartilage tissue, ossified cartilage, and enchondromas. Chondrosarcoma of the trachea is the least-studied tumor, with only 35 cases described in the literature from 1959 to 2020. Surgery with R0 resection remains the gold standard treatment of tracheal chondrosarcoma. The median age of patients at the time of diagnosis was 68 years, and 91 % were male. The most common symptoms at the initial visit were dyspnea (up to 80 % of cases). Tumors located in the proximal third of the trachea were observed in 54 % of cases, while tumors in the distal third of the trachea were found in 29 % of cases. Low-grade tumors (g1) were the most common (54 %). Computed tomography of the chest is considered the gold standard for the detection of tracheal tumors. Purpose: To demonstrate a successful case of treatment of tracheal chondrosarcoma. Case presentation. A 67-year-old male patient was diagnosed with a tracheal tumor. On 04.07.2022, surgical treatment was performed: circular resection of the 2nd, 3rd, and 4th tracheal rings with lymph node dissection of the regional paratracheal lymph nodes R0. The postoperative period was uneventful. Adjuvant therapy was not given. At the 2-year follow-up, no anastomotic complications were reported. Conclusion. To date, circular resection of the trachea (R0) with end-to-end tracheal anastomosis is the gold standard for treating tracheal chondrosarcoma. this approach was performed in 77 % of cases with the median follow-up time of more than 30 months and relapse rate of only 6 %. It should be noted that adjuvant chemotherapy was not used in these cases due to the extremely low sensitivity of the tumor to chemotherapy drugs.